Support for the environmental sustainability of cities and settlements through taxation tools ("Journal "U". Economy. Management. Finance.", 2025)
The article explores the potential of using fiscal instruments to stimulate the environmental sustainability of cities and settlements. Based on the analysis of Russian and international experience, the author has developed a comprehensive model of environmental taxation that takes into account the specifics of urbanized territories. The proposed system of tax mechanisms is aimed at reducing the negative impact on the environment, stimulating the introduction of green technologies, and optimizing the use of natural resources in the urban environment.
Keywords: environmental taxation; sustainable development of cities; green economy